Development of Contextual English Language Teaching Materials Based on Sport Coaching Education - Burhan, Kristian; Amsa, Helfany; Astuti, Indri; Franchisca, Sherly (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2025)
Despite the prominent role of English in the sports industry, few studies have explored the demand for English competence among future sport coaches, especially in the context of an increasingly globalized sporting domain where communication is becoming key in diverse trading environments. However, the students who are studying Sport Coaching Education typically do not have English skills that are specifically focused on real-life coaching situations. This study is developing teaching materials for teaching English language using the Contextual Teaching and Learning (CTL) approach specifically for the needs of the Sport Coaching Education students. In this study, a Research and Development (R&D) design based on the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model was used through a needs analysis, material development, expert validation, and pilot testing. The needs analysis indicated a considerable gap between students’ current English material and the communicative needs of the sport coaching specialism. The students were mostly interested in sport-specific vocabulary and more speaking practice in coaching contexts. The materials developed involved listening, speaking, reading and writing activities based on authentic coaching situations. Expert reviews scored the materials favorably (4.6/5 score on average) on relevance, pedagogical effectiveness, and feasibility. It concludes that contextual, sport-specific English resources are useful for improving language competence and coaching preparedness. Linking ESP to real-world practice ensures that CTL serves as far more than just an academic pursuit in sport coaching education, connecting them far more directly with the professional world. Keywords: contextual language teaching; need analysis; sport coaching education; ESP